Recognition of factors that promote resilience to hurricanes. Issue 2 (1st June 2021) - Lucero Álvarez, Adolfo; Alviso, Columba Rodríguez; Frausto Martínez, Oscar; López, José Luis Aparicio; Díaz Garay, Alejandro; Reyes Umaña, Maximino
Abstract: The economic damage and loss of lives caused by hurricanes have motivated efforts to expand scientific research related to resilience to these natural phenomena. However, published writings are dispersed and fragmented in different fields of study. This research is aimed to identify factors that promote resilience in hurricane-impacted areas by reviewing specialized literature. The study is qualitative, based on content analysis. Twenty-seven articles published between 2006 and 2019 were reviewed. The results show that resilience has a multidisciplinary character, although there is a coincidence in defining it as a system's ability to absorb, resist, and recover from disasters; the system is conceived as the representation of a totality made up of related elements (ecological, social, and economic, among others). A focus on physical infrastructure predominates, but a social approach begins to be distinguished. The factors that promote resilience are grouped into four categories: ecological, social, infrastructure, and mental health. Resumen: La investigación científica sobre resiliencia ha incrementado paralelamente a los daños económicos y casualidades humanas generadas por el paso de huracanes. El objetivo de esta investigación es identificar los factores que promueven la resiliencia en áreas impactadas por huracanes, mediante la revisión de literatura especializada. El estudio es cualitativo basado en análisis de contenido de publicaciones científicas en diferentes campos de estudio. En específico, se revisaron veintisiete artículos publicados entre 2006 y 2019. La resiliencia es multidisciplinar y hay una coincidencia al definirla: la capacidad de un sistema para absorber, resistir y recuperarse de los desastres. Predomina un enfoque de infraestructura física, pero comienza a distinguirse uno social. Los factores que promueven la resiliencia se agrupan en cuatro categorías: ecológica, social, infraestructura y salud mental. Résumé: Les pertes en vies humaines et les dégâts économiques causés par les ouragans ont motivé la recherche scientifique sur la résilience, définie comme la capacité d'un système à absorber, à résister et à se remettre des catastrophes. Les écrits publiés sont dispersés et fragmentés dans différents domaines d'étude. L'objectif de cette recherche était d'identifier les facteurs favorisant la résilience dans des zones touchées par les ouragans en examinant la littérature spécialisée. L'étude est qualitative, basée sur une analyse de contenu. Vingt-sept articles publiés entre 2006 et 2009 ont été examinés. L'approche en termes d'infrastructure physique prédomine, mais une approche sociale commence à se distinguer. Les facteurs favorisant la résilience peuvent être regroupés en quatre catégories : écologique, sociale, infrastructurelle et celle de la santé mentale.